Integrated Digital and Conventional Treatment Workflow in Guided Complete Mouth Implant Rehabilitation: A Clinical Case Report - Lee, Jason D. (Dent J (Basel), 2019)
CLINICAL IMPLICATIONS: The integration of both conventional and digital techniques in the treatment workflow can have a synergistic effect that facilitates the treatment of complex complete mouth prosthetic rehabilitations. ABSTRACT: The introduction of digital dentistry and CAD/CAM technology has redefined treatment concepts in implant dentistry—computer guided implant placement has become routine practice, and CAD/CAM prostheses are now commonplace. These advances in treatment options and modalities has led to a paradigm shift in the workflow of surgical and restorative treatments. This case report presents a customized staged treatment protocol that involves the strategic retention of teeth to serve as transitional abutments, which will support a computer guided implant surgical guide as well as a fixed interim prosthesis. The treatment protocol also describes an integrated digital and conventional workflow for full mouth implant-supported fixed prosthetic rehabilitations to provide improved patient care with more predictable outcomes and fewer complications.